Anti‐migratory activity of marine alkaloid monanchocidin A – proteomics‐based discovery and confirmation. Issue 10 (27th April 2016) - Dyshlovoy, Sergey A.; Venz, Simone; Hauschild, Jessica; Tabakmakher, Ksenya M.; Otte, Katharina; Madanchi, Ramin; Walther, Reinhard; Guzii, Alla G.; Makarieva, Tatyana N.; Shubina, Larisa K.; Fedorov, Sergey N.; Stonik, Valentin A.; et al.
Abstract : Monanchocidin A (MonA) is a novel marine alkaloid with promising anti‐cancer properties. We recently demonstrated its high efficacy in human urogenital cancers including germ cell tumors. Here, we applied a global proteome screening approach to investigate molecular targets and biological processes affected by MonA in the human cisplatin‐resistant germ cell cancer cell line NCCIT‐R. Bioinformatical analysis of the proteomics data predicted an effect of MonA on cancer cell migration. Thus, proteins known to be involved in cancer cell migration and invasion were chosen for further validation. The protein alterations identified by proteomics resulted from both, regulation of the total protein expression and post‐transcriptional modifications. Among others, regulation of an isoform of vimentin, up‐regulation of multiple apolipoprotein E isoforms, and inhibition of hypusination of eukaryotic translation initiation factor 5A‐1 were found upon treatment with MonA. Further functional analyses were performed and revealed decreased cell migration and colony formation of cancer cells treated with MonA at non‐cytotoxic and non‐antiproliferative concentrations. This work provides further insights into the molecular mechanisms behind MonA bioactivity. Furthermore, our research is exemplary for the ability of proteomics to predict drug targets and mode of action of natural anti‐cancer agents.